UJI DAYA HAMBAT EKSTRAK ETANOL DAUN RAMBAI (Sonneratia Caseolaris (L) Engl) TERHADAP BAKTERI Propionibacterium acnes DAN Staphylococcus epidermidis - Fitriani, Tiya; Nashihah, Siti (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Currently there are many anti-acne preparations on the market but not a few of these drugs give side effects to the user. The need for alternatives from nature that can act as antibacterial in the treatment of acne that has a smaller risk of side effects. This study aims to determine the inhibition of ethanol extract of rambai leaves (Sonneratia caseolaris (L) Engl) against acne-causing bacteria Propionibacterium acnes and Staphylococcus epidermidis. Extraction was carried out by the UAE method and a yield of 9.21% was obtained. Phytochemical screening obtained positive results containing flavonoids, triterpenoids, tannins, saponins and phenol compounds. Antibacterial activity test was conducted using the well diffusion method with 4 different concentrations of 15%, 25%, 50% and 75% with positive control of clindamycin 0.03% and negative control of DMSO 1%. The results of antibacterial activity testing on Propionibacterium acnes bacteria obtained inhibition zone diameters of 3.3 mm; 4.43 mm; 6.48 mm; and 8.45 mm, respectively, while on Staphylococcus epidermidis bacteria 11.08 mm; 12.27 mm; 15.38 mm; and 16.78 mm, respectively. The results of the One Way ANOVA statistical test obtained a significance value of 0.000 (p<0.05) which indicates that the treatment of each group is significantly different.